Face-to-Face Education vs. Group Education on Knowledge and Anxiety of Patients Undergoing Coronary Angiography - Hamid Haghani; Mahnaz Seyedoshohadaei; Nooredin Mohammadi; Mona Tizhoosh (Tehran University of Medical Sciences, 2012)
Background & Aim: Lack of knowledge about coronary angiography may cause anxiety and stress in patients. Implementing appropriate educational methods can be effective in decreasing the level of anxiety among these patients. This study aimed to compare the effects of face-to-face with group education on anxiety and knowledge of patients undergoing coronary angiography. Methods & Materials: This quasi-experimental study was conducted in Shaheed Rajaie Cardiovascular Center affiliated to Tehran University of Medical Sciences in 2012. Through consecutive sampling method, 84 hospitalized patients who were candidate for coronary angiography were selected and allocated into two educational groups. Data were collected using a demographic data sheet, the knowledge assessment questionnaire, and the Spielberg state-trait anxiety inventory. Patients in both groups received same educational content. The patients' knowledge and anxiety were assessed before and after the intervention. Data were analyzed using descriptive statistics and independent t-test and paired t-test. Results: The finding showed that both face-to-face education and group education were effective in enhancing the knowledge of the patients. However, group education was more effective than the face-to-face education in reducing the patients' anxiety (P=0.049). Conclusion: Health professionals, particularly nurses, can use group education as an effective and appropriate strategy to improve patients' knowledge and to reduce the anxiety among patients undergoing coronary angiography.